Characterization Evaluation of Clove Flower Oil (Syzygium aromaticum (L.) Meer) And Pharmacological Properties Of Anthelmintic - Cut Suraiya Wahyuni Utami; Ummu Balqis; Farida Athaillah; Muhammad Hanafiah; Cut Dahlia Iskandar (The Faculty of Veterinary Medicine of Syiah Kuala University, 2019)
Clove oil is distilled from clove flowers (Syzigium aromaticum) and characterized by physical properties and GC-MS. Distillation was carried out by steam distillation method for 8 hours. Analysis of clove oil was carried out by GC-MS method. The distillation results obtained 163 mL of clove oil with physical properties that meet the requirements of SNI 06-4267-1996. The results of the analysis using GC-MS showed that clove oil contained 6 components, namely, Eugenol 88.20%, Alpha Copaene 0.49%, Caryophyllene 3.77%, Alpha Humulene 0.48%, Eugenyl acetate 6.76%, and Caryophyllene Oxide 0.30%. Another fact shows that clove flower oil has anthelmintic activity.